1994
DOI: 10.1017/s174275840001674x
|View full text |Cite
|
Sign up to set email alerts
|

Sources and mechanisms of resistance to sorghum head bug, Eurystylus immaculatus Odh. in West Africa

Abstract: Printed ~n Ken!,a. All rights resr.r\ed SOURCES AND MECHANISMS OF RESIS'I'AN('E: 'TO SOR(;HIIM HEAD RUG, EURYSTYLL'S I~%lhlAC~~I.ATL!S 0I)H. I N WKS.1' AFRICA Abstract-Sorghum i s one of the most in1port;lnt cereal crops in West Africi~, i~n d t11e heed 1)up. Burystylus intntac111urir.s Odh. (Hemiptera: 5liridac.) i s the ke) pest of gri~iri sorghuni in this region. range of sorghuni genotypes \\ere cv;~luated for resistance to sorgliurn he;ltl bug 111 Sotlrt~;~ (hlali and Karnboinse (Hurkina Faso). (;enotypcs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Both years, five panicles at the grain maturing stage (3 weeks after half-anthesis) were randomly chosen from the first central row of each plot, and successively shaken in a polyethylene plastic bag so as to dislodge all insects present (Sharma et al 1994). The total number of Eurystylus bugs (adults and nymphs) was then determined.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both years, five panicles at the grain maturing stage (3 weeks after half-anthesis) were randomly chosen from the first central row of each plot, and successively shaken in a polyethylene plastic bag so as to dislodge all insects present (Sharma et al 1994). The total number of Eurystylus bugs (adults and nymphs) was then determined.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, data from Tioribougou in 1998 were not considered since the sampling was not conducted in time. In addition, five panicles randomly chosen from the second central row of each plot were visually scored for bug damage, using a 1-9 rating scale, where 1 = all grains fully developed with less than 10% showing a few bug feeding punctures, and 9 = more than 75% grains remaining undeveloped and barely visible outside the glumes (Sharma et al 1994;Ratnadass et al 2002).…”
Section: Data Collectionmentioning
confidence: 99%
“…, ; Smith ) such as grapevine phylloxera ( Phylloxera vitifoliae ) (Painter ), cotton jassid ( Amrasca biguttula ) (Sundramurthy & Chitra ), sorghum shoot fly ( Atherigona soccata ) (Sharma ), and sorghum head bug ( Eurystylus oldi ) (Sharma et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…HPR to insect was a principal method of insect control before the chemical insecticide era. Previous studies have reported the deployment of insect-resistant varieties for the control of insect pests (Maxwell & Jennings 1980;Sharma et al 1999aSharma et al , 1999bSmith 1989) such as grapevine phylloxera (Phylloxera vitifoliae) (Painter 1951), cotton jassid (Amrasca biguttula) (Sundramurthy & Chitra 1992), sorghum shoot fly (Atherigona soccata) (Sharma 1993), and sorghum head bug (Eurystylus oldi) (Sharma et al 1994). In this study, some of the leguminous crop cultivars such as cowpea cultivar Jangchae and soybean cultivar Daewon exhibited a higher level of insect resistance.…”
Section: Relationships Between Development and Survival And Ovipositionmentioning
confidence: 99%
“…However, loose-panicled genotypes are also badly damaged when head bug infestation is high (Sharma, 1985;Sharma et al, 1993a). On the other hand, midge damage has been reported to be low in compact-panicled genotypes (Murty and Subramaniam, 1978).…”
Section: Introductionmentioning
confidence: 99%